LEGAL PROTECTION FOR INVESTORS AGAINST INSIDER TRADING PRACTICES BY ISSUERS ON THE CAPITAL MARKET: Comparative Study between Indonesian and U.S. Capital Market - Sembiring, Theo Pangarapenta; Sinaulan, Dr. Ramlani Lina (jfpublisher, 2024)
Transparency of information in stock trading is concerned with all information about the business affairs of a company that is going to become more popular, which is owned by the company to the wider community. The efforts that can be conducted to realize the principle of information disclosure in the capital market are public companies must provide the correct prospectus, which is written information related to the public offering. Infringements of this principle can lead to abnormalities in the capital market, one of which is insider trading practices where insiders or corporate insiders conduct securities transactions by using exclusive information and the information is unavailable to the public or investors. In addition, this practice is also an unfair trading practice due to the inside trader’s superior position (in information ownership) compared to other investors. This research uses normative juridical research methods that focuses on studies related to the implementation or application of rules or norms contained in positive law. There are several approaches commonly used in legal research such as statute approach, case approach, comparative approach. Data collection in this research will be conducted by library research on secondary data. This research will use a qualitative normative analysis method. The research indicated that controlling insider trading is quite difficult because it is impossible to know when it began, the number of transactions, and the amount of losses. Legal protection against insider trading can be preventive or repressive. Preventive protection aims to prevent violations through legislation, while repressive protection provides sanctions such as fines or additional penalties after a violation occurs. Law enforcement in capital market activities consists of administrative sanctions, criminal sanctions, and civil compensation claims.